EFFECTIVENESS OF CONVERSATION THERAPY (DIALOGIC APPROACH) IN CHILDREN WHO STUTTER - Abdullayeva Karomat Islom qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article examines the effectiveness of conversation therapy using a dialogic approach for children who stutter. The study analyzes how structured dialogues, interactive communication, and guided conversations can improve speech fluency, reduce anxiety, and enhance emotional stability. The integration of dialogic techniques with traditional speech therapy is explored, highlighting their role in increasing motivation, fostering self-confidence, and supporting social communication skills. Results indicate that a dialogic approach provides a supportive environment that significantly contributes to speech improvement and overall communicative competence in children who stutter.